The application of interactive Task-Based Learning for EFL students - Eny Syatriana; Ardiansyah; Richard Orem (International Journal of Humanities and Innovation (IJHI), 2018)
Speaking plays an essential role in the production of a variety of languages, it can be in the form of discussions, speeches, debates, argumentation, conversation, storytelling and retelling. However, this study aims to develop a learning strategy based on Task Based Learning that can improve speaking ability. The Research questions are (1) what learning strategy is appropriate to increase the students speaking skills? (2) How is the student achievement under the implementation of task-based learning (3) is the application of task-based learning effective in improving students’ ability to speak? The study consists of (1) need analysis, (2) design strategy, (3) implementation, and (4) evaluation. The study will be implemented in three steps using design development research. The principles and procedures are using qualitative and quantitative. The participant of the research was a speaking class subject of UNISMUH. The study concludes that although the participants have shown their ability to speak using Task Based Learning improvement is needed to increase fluency, accuracy, flexibility, comprehensibility, appropriately, and effectively to make their speaking better. Recommendation to English lecturer also given as pedagogical implication of this study.